Pédagogies féministes et didactique des langues-cultures : des liens à construire - Sophie Bailly; Véronique Lemoine-Bresson; Carine Martin (Glad!)
This interview with the members of the Giflex research group, created in 2020 at the University of Lorraine within the laboratory CNRS ATILF, focuses on the reflections of three teacher-researchers in Didactics of Language and Culture who are grappling with the notions of gender and feminism in their teaching. They address theoretical questions, as well as practical examples and present current research projects.